MORAL ASPECTS IN THE NOVEL DIARY PRAMUGARI 1 “MAKNA CINTA & KEHIDUPAN” BY AGUNG WEBE - Fitriani; La Ode Syukur; Andi Muhammad Ruum Sya'baan (Jurnal Casa Cendekia, 2025)
The purpose of this study is to describe the moral aspects in the novel Diary Pramugari 1 by Agung Webe. This study is a literature study, and the method used in this study is descriptive qualitative. The data in this study is the novel Diary Pramugari 1 by Agung Webe. The source of this research is the text of the novel Diary Pramugari 1 by Agung Webe, first edition published in 2018 by Pohon Cahaya, in Yogyakarta. The data collection technique used in this study is the reading and note-taking technique. Data analysis in this study uses a structural approach. The method used in this study is a qualitative descriptive method. Descriptive means describing or depicting data systematically, accurately, and as it is, in accordance with objective reality based on the data contained in the novel Diary Pramugari 1 by Agung Webe. Furthermore, qualitative means describing concepts of understanding that are related to one another, conveyed verbally and guided by theories relevant to the object of study in this research. The results obtained from the moral aspects in Agung Webe's novel Diary Pramugari 1 are: (1) the moral aspect of responsibility, (2) the moral aspect of justice, (3) the moral aspect of following rules, and (4) the moral aspect of responsibility for completing tasks.